Race mixture in nineteenth-century U.S. and Spanish American fictions : gender, culture, and nation building - Rosenthal, Debra J., 1964- (University of North Carolina Press, 2004)
Race mixture has played a formative role in the history of the Americas, from the western expansion of the United States to the political consolidation ofLatin America. This text examines 19th-century authors in the United States and Spanish America who struggled to give voice to contemporary dilemmas about interracial sexual and cultural mixing.